2015
DOI: 10.4103/0970-9290.162883
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of salivary glucose, amylase, and total protein in Type 2 diabetes mellitus patients

Abstract: These results suggest that diabetes influences the composition of saliva. Since a significant correlation was not observed between salivary and blood glucose levels, further research is needed to determine salivary glucose estimation as a diagnostic tool for diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
2
12
1
4
Order By: Relevance
“…The obtained data are consistent with the results obtained in children with type 1 diabetes [9,11–14,21] and adults with type 2 diabetes. [16,22] We found no significant differences in the salivary flow rate between D1 and D2 with regard to the level of metabolic control, similar to the data obtained in diabetic children. [11,14] Comparing D1 and D2 with regard to disease duration, no significant differences in salivary secretion were noticed, similar to children with type 1 diabetes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The obtained data are consistent with the results obtained in children with type 1 diabetes [9,11–14,21] and adults with type 2 diabetes. [16,22] We found no significant differences in the salivary flow rate between D1 and D2 with regard to the level of metabolic control, similar to the data obtained in diabetic children. [11,14] Comparing D1 and D2 with regard to disease duration, no significant differences in salivary secretion were noticed, similar to children with type 1 diabetes.…”
Section: Discussionsupporting
confidence: 85%
“…[15,19,20] Numerous salivary components have been studied in relation to DM, to its duration, and metabolic control. The following findings have been reported when diabetic patients were compared with the control group: lower pH, [16,21] higher [11–14,16] or lower total protein concentration, [20,22] higher glucose level, [12,13,16,20,22] higher [21,23] or lower calcium level, [13,16] higher sodium and potassium level, [16] higher phosphate and magnesium levels, [23] the same concentration of creatinine, [23] higher urea, [13] lower α-amylase, [16,22] higher [2325] or the same [26] levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT), higher [14,23] or the same level of lactate dehydrogenase (LDH), [26] higher level of salivary antioxidants, [9] higher salivary IgA, [12] the same level of salivary antimicrobial factors (except for salivary peroxidase), [18] and increased myeloperoxidase activity and IgA content. [15] …”
Section: Introductionmentioning
confidence: 97%
“…The studies were published from 1996 to 2017. Two studies were reported in Turkey,[ 14 15 ] one in Pakistan,[ 16 ] three in Iran,[ 3 17 18 ] thirteen in India,[ 4 6 9 19 20 21 22 23 24 25 26 27 28 ] one in Brazil,[ 29 ] two in Nigeria,[ 30 31 ] one in Egypt,[ 5 ] one in Poland,[ 32 ] and one in China. [ 33 ] There were 1432 and 900 diabetic patients and healthy controls in all studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age and percentage of the males in both groups are shown in Table 1 . Nine studies measured the salivary profile of patients and controls in non-fasting condition (<2 h)[ 8 14 19 21 22 24 26 29 32 ] and 16 studies in fasting (8–12 h) condition. [ 3 4 5 6 9 15 16 17 20 23 25 27 28 30 31 33 ] Three studies reported SE,[ 15 17 27 ] one study reported median/range,[ 19 ] one study reported two means/SDs,[ 16 ] and a few studies reported different units, which were changed.…”
Section: Resultsmentioning
confidence: 99%
“…After a 12 h fast animals were orally gavaged with 2g/kg body weight of glucose dissolved in water. Blood samples were collected at 0, 30, 60 and 120 min for measurement of FBG levels by the glucose oxidase method [ 28 ]. After 4 weeks of treatment, mice were fasted for 12 h and blood collected from the orbital venous plexus and plasma separated by centrifugation at 3500g for 15 min.…”
Section: Methodsmentioning
confidence: 99%